Utilization of Chatbot Telegram AI to Promote Students' Creative and Innovative Entrepreneurship in Learning Context - Elisa Betty Manullang; Rita Hartati; Rafika Dewi Nasution (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2023)
The development of technology in the current era is advancing very rapidly. Along with digital learning materials, they can increase verbal communication and various visual, audio and motion texts. This study aims to develop students' 4C competencies (Creativity and Innovation, Critical Thinking and Problem-Solving, Communication and Collaboration) in 21st-century learning through creative entrepreneurship learning materials of the Telegram Chatbot Artificial Intelligence with Natural Language Processing (NLP) Method. The scope learning materials are focused on Personal Business Plans, Customer Interviews, Customer Observation, Selling Products, and being a Creative Entrepreneur, which will be uploaded to the Telegram Chatbot as e-learning students' material. This research will use the Research and Development approach of Borg and Gall (1983). The series of research and development steps are carried out in stages, and each action will be taken to the results of the previous step until a new development product of learning materials is finally obtained. Product development design of the preliminary stage needs analysis is carried out by collecting related data and developing Creative Entrepreneurship learning materials for the Telegram chatbot model. The Creative Entrepreneurship learning program will involve 50 students of the English Literature Department, Universitas Negeri Medan, to analyze the feedback from the questionnaire Google form.